Utilizing Key Opinion Leaders in Social Media Marketing: Improving Guest Satisfaction and Influencing Booking Choices - Slamet Jumheri,; Tuti, Meylani; Riyanto, Agus (Technium Social Sciences Journal, 2025)
This study aims to analyze the role of Key Opinion Leaders (KOLs) and social media marketing in influencing guest satisfaction through stay decisions. This study uses a quantitative approach. The population in this study were guests of 3-star hotels in Jakarta, with a purposive sampling technique, namely, guests who have stayed more than twice. The study included 200 respondents. The results showed that KOL and social media marketing had a significant influence on stay decisions and guest satisfaction, with KOL having both direct and indirect effects. However, the mediation effect of stay decisions on satisfaction was not significant. These findings indicate that hotel marketing strategies through collaboration with KOL and social media marketing increase guest satisfaction because promotional expectations are in accordance with the experience felt by guests.